INVESTIGATION OF ADSORPTION OF DIMETHYLSULFOXIDE ON SURFACE SILICA BY IR SPECTROSCOPIC AND GRAVIMETRIC METHODS (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
Adsorption dimethylsulfoxide (DMSO) on a surface partly dehydroxileted especially pure silica were investigated by infrared spectroscopic and gravimetric methods. It is shown, that the initial centers of adsorption DMSO is basically superficial intense the siloxan groups forming by thermal vacuum of SiO2. In the process of interactions of these groups with enol form DMSO at room temperature, occurs chemisorption of the last one, with formation superficial-connected methylenmethylsylfoxyde compounds, maximal superficial density of which is observed on samples of a sorbent, preliminary termovacuuming at 600°C.
Keywords: surface partly dehydroxileted; methylenmethylsylfoxyde; pure silica; DMSO